Logistics infrastructure management in the system of digital transformation of the economy of Ukraine - Kostiuk, Viktoria; Khudolii, Artem; Korniiko, Yana; Petrenko, Olha; Dybchuk, Liudmyla; Shmatkovska, Tetiana (Magnanimitas AG, 2024)
The article examines the main aspects of the digitalization of logistics processes in the context of their impact on the efficiency and competitiveness of enterprises. It explores technological innovations such as the use of big data, the Internet of Things, and blockchain, which are changing approaches to supply chain management. The role of government policy in supporting digital logistics initiatives is analyzed, and the industry’s key challenges are identified. The main directions for implementing digital innovations in global logistics networks have been determined. Factors that negatively affect the implementation of digital solutions in the activities of logistics enterprises are considered. The necessity of implementing digital technologies to optimize logistics processes and increase the stability of Ukraine’s economy in the face of global changes has been proven.
Keywords: logistics; logistics infrastructure; national economy; digitalization of the economy; sea transport; land transport; logistics infrastructure management; digital transformation